2017
DOI: 10.1016/j.geothermics.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Regression-based reduced-order models to predict transient thermal output for enhanced geothermal systems

Abstract: Reduced-order modeling is a promising approach, as many phenomena can be described by a few parameters/mechanisms. An advantage and attractive aspect of a reduced-order model is that it is computational inexpensive to evaluate when compared to running a high-fidelity numerical simulation. A reduced-order model takes couple of seconds to run on a laptop while a high-fidelity simulation may take couple of hours to run on a high-performance computing cluster. The goal of this paper is to assess the utility of reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Due to significant costs involved in field trials of HDR reservoirs [7], computational modelling is deemed to be an affordable option to enable researchers to investigate possible ways to extend the use of EGS particularly during the preliminary stages to assess the thermal power and the economic feasibility of EGS sites [7]. A comprehensive study conducted by [16] on numerical modelling of EGS reservoirs, indicated that, in general, modelling can be divided into three different categories in terms of EGS reservoir performance. The first category relates to improving the efficiency of heat extraction technologies for different rock deposits considering a wide range of contributing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to significant costs involved in field trials of HDR reservoirs [7], computational modelling is deemed to be an affordable option to enable researchers to investigate possible ways to extend the use of EGS particularly during the preliminary stages to assess the thermal power and the economic feasibility of EGS sites [7]. A comprehensive study conducted by [16] on numerical modelling of EGS reservoirs, indicated that, in general, modelling can be divided into three different categories in terms of EGS reservoir performance. The first category relates to improving the efficiency of heat extraction technologies for different rock deposits considering a wide range of contributing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning (ML) is a widely used tool for extracting features [16,17] and classifying seismic signals. In addition to earthquake detection and prediction [10,13], ML is shown to be successful in various other subsurface applications [18][19][20][21][22][23]. Within the context of ML, there are many available techniques that are able to predict the evolution of time-series and distinguish seismic signals, within a certain tolerance [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prevalence of brittle materials in several applications in geosciences (e.g., hydraulic fracturing, geothermal, etc.) [7][8][9], infrastructure [5] and aerospace industry [10], fast and accurate models of brittle fracturing are needed.…”
Section: Introductionmentioning
confidence: 99%